URGENSI USUL FIKIH DALAM PERKEMBANGAN LEMBAGA KEUANGAN SYARIAH (STUDI PELAKSANAAN PENETAPAN BESARAN INFAK ATAS PEMBIAYAAN DI BMT NURUL HUSNA BATANGHARI LAMPUNG TIMUR) - Reonika Puspita Sari (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2018)
Academics and practitioners of Islamic financial institutions, are not enough just to know the fiqh of muamalah and its application, but more important is to understand the fiqh proposal of each product in financing in Islamic financial institutions, for example in submitting financing capital for a business. For Islamic Financial Institutions, with the provision of this financing capital, they can play capital funds into the real sector and can help those who need business capital. Baitul Maal Wat Tamwil for example, in its operation the institute is projected to manage funds developed for micro-enterprises and manage virtue funds or social funds (Zakat, Infaq and Sedekah). This paper aims to explain the urgency of the fiqh proposal in the development of sharia financial institutions in determining the amount of infaq for financing at BMT Nurul Husna Batanghari in East Lampung, and outlines the solution to improving financial institutions (BMT Nurul Husna Batanghari) to be truly in accordance with Islamic law. . This study uses descriptive qualitative research methods, with data collection techniques using interviews, observation and documentation. As a result, in the development of Islamic financial institutions in determining the amount of infaq for financing at BMT Nurul Husna Batanghari, East Lampung, until now it has not been in accordance with Islamic law. The BMT stipulates the infaq amount of 10% of the amount of financing to customers. This is contrary to the provision of issuing infaq in Islamic law which is not determined and is voluntary. The implementation of the infaq to win mutual agreement between the customer and the BMT and not violate the provisions of Islamic law, can be done by the BMT when making contracts to customers in financing transactions, preferably voluntary, does not specify the amount of infaq that must be issued by the customer, and BMT must provide explanation of the distribution of infaq funds to customers when financing contract transactions